Assessment of Green-Lipped Mussel Perna Viridis (Linnaeus) As a Biomonitoring Agent of Cadmium, Copper, Mercury, Lead and Zinc for the West Coast of Peninsular Malaysia - Yap, Chee Kong (2003)
Sediment samples (46 sites) and green-lipped mussels Perna viridis (L.) (19 sites) from the west coast of Peninsular Malaysia were sampled between 1998 and 2001 and were analyzed for Cd, Cu, Hg, Pb and Zn. The mean levels of the metals in the west coast (offshore: intertidal) sediments were 0.75 ± 0.06 : 0.86 ± 0.11 µg/g dry weight (dw) for Cd, 4.27 ± 0.36 : 29.22 ± 8.84 µg/g dw for Cu, 38.87 ± 2.93 : 60.10 ± 9.47 µg/g dw for Hg, 17.36 ± 0.99 : 23.32 ± 3.39 µg/g dw for Pb and 37.22 ± 2.01 : 84.64 ± 12.62 µg/g dw for Zn. The metal levels in the soft tissues (ST) of P. viridis were found to be 0.25-1.35 µg/g dw for Cd, 6.31-20.21 µg/g dw for Cu, 20.00-152.00 µg/g dw for Hg, 1.27-8.76 ug/g dw for Pb and 53.82-135.50 µg/g dw for Zn. All these metal levels were relatively low in comparison with previously published regional data. In general, the metal levels were higher in the intertidal sediment than in the offshore sediment. Geochemical studies in the sediments revealed that about 58.6 : 57.7% for Cd, 53.3 : 46.3% for Cll, 72.6 : 54.3% for Pb and 34.5 : 48.7% for Zn, in the offshore and intertidal sediments, respectively, were most likely due to anthropogenic sources. Localized elevations of heavy metals in a few locations indicated that the offshore and intertidal areas of the west coast of Peninsular Malaysia were likely to have received anthropogenic metals. By using the protein level a1lozyme approach, the genetic differentiation among the different geographical populations of this species fell within the range for conspecific populations. Since P. viridis populations are sedentary, widely distributed in the west coastal area of Peninsular Malaysia and have low genetic differentiation, the species generally is a good biomonitoring agent for heavy metals in the area. The mussel P. viridis collected from the field also showed that the metal concentrations in its total ST were positively and significantly (P< 0.05) correlated with Cd, eu and Pb in the environment as represented by the sediment samples. The suitability of P. viridis as a biomonitoring agent for heavy metals was experimentally studied. The results of the laboratory experiments showed that the ST of P. viridis was readily capable of accumulating heavy metals especially Cd, Pb and Hg to elevated levels. Depuration studies also showed that the metal levels in different STs were significantly (P< 0.05) correlated with those of the seawater. By using endpoints mortality, filtration rate (FR) and condition index (CI), P. viridis was found to be a sensitive but tolerant organism to Cd, Cu, Pb and Zn. The byssus (BYS) of P. viridis was found to be a sensitive biomonitoring tool for Zn whereas its total shell was a good biomonitoring material for Cd and Pb. Allozyme polymorphism of P. viridis was found to be a potential biomarker for metal contamination. Simple indicators (aerial exposure and shell deformities of P. viridis) for heavy metal pollution were also identified.